The Buddha's wizards : magic, protection, and healing in Burmese Buddhism - Patton, Thomas Nathan (Columbia University Press, 2018)
Belief in wizard-saints who protect their devotees and intervene in the world is widespread among Burmese Buddhists. The Buddha's Wizards is a historically informed, ethnographic study that explores the supernatural landscape of Buddhism in Myanmar to explain the persistence of wizardry as a form of lived religion in the modern era.